PERAN DAN FUNGSI PERPUSTAKAAN NASIONAL DI IBU KOTA NEGARA BARU KESATUAN REPUBLIK INDONESIA - Irhamni Irhamni; Vira Farhana (Perpustakaan Nasional RI, 2020)
The Government of the Republic of Indonesia declaration to move the apital city from Jakarta to Kalimantan. The capital move has also been carried out in a number ofcountries like Japan which moved its capital from Kyoto to Tokyo and the United States from Pennsylvania to Washington DC. This transfer will certainly have an impact on the role of the function of the National Library because there will be many significant changes in terms of population demographics and so forth. This paper will try to see how the role and function of the national library in the new national capital of the Republic of Indonesia by looking at the role of national libraries in the United States and Japan. The data in this study were taken through study studies, interviews and discussion group forums held at the Japanese Diet Library and the Library of Congress in Washington DC, meanwhile the data processing only included descriptive analysis related to how the role and function of national libraries in the country ever experiencing the relocation of capital in the world. The National Library in the new capital city needs to be repositioned as a reference and deposit center for research and studies for state policy makers. a number of challenges that will be faced are changes in the behavior of users and strengthen the position of the national library as a research reference node in Indonesia